The enduring consequences of conflict-related sexual violence: a qualitative study of women survivors in northern Uganda - Mahlet A. Woldetsadik; Grace Acan; Okwir Isaac Odiya (Conflict and Health, 2022)
Abstract Background One in three women in northern Uganda report having suffered from conflict-related sexual violence (CRSV), including forced marriage and rape. Research on the long-term effects of CRSV on the health and social well-being of survivors is scant, but crucial to informing policy and improving programs tailored to conflict-affected communities. Understanding women’s perceptions of and experiences with CRSV, especially related to the persistent health and social challenges they continue to face, is critical for developing effective and targeted interventions. Methods We worked with a local, survivor-led organization to recruit participants purposively from three post-conflict districts in northern Uganda: Gulu, Lira, and Pader. Women who had experienced CRSV and who were 18 years of age or older were eligible to participate. We asked participants open-ended questions about their experience with CRSV, including how it continues to affect their health and social well-being, any impact it had on their relationships, and if they faced barriers to accessing services. We transcribed, translated, and uploaded interview responses to the qualitative data analysis software MAXQDA and analyzed data thematically using a modified approach to grounded theory. Results We conducted 30 interviews between October 2016 and March 2017. All participants reported experiencing forced marriage, rape, or forced pregnancy. Over two-thirds of participants said they continued to face physical and psychological issues, including untreated sexually transmitted infections, anxiety, and depression. Almost half of the women faced challenges with maintaining links with family members, stigma related to their experiences during abduction that also extended to their children born in captivity, and difficulty with accessing and affording health care. Barriers to seeking care included fear of disclosure and being unable to find services. Women identified peer-support from other survivors as a key coping mechanism. Conclusions Women survivors continue to face multifaceted health and social problems in the post-conflict period. Most health-related programs that were set up at the end of the war in northern Uganda are no longer available. Increasing access to care, particularly services tailored to treating chronic reproductive health issues and mental health, is paramount for women survivors in northern Uganda and other conflict-affected regions.